Appreciation, Analysis and Creation in the Teaching-learning of the Plastic Arts - Soriano, Leandro Ernesto Prado; Montero Zayas, Geovannys; Šurín, Stanislav; Jenisová, Zita (Journal of Education Culture and Society, 2024)
Aim. The Didactics of the Plastic Education is necessarily nourished by the general didactics and the arts, as well as by their particular methodologies, in aspects related to the teaching-learning of the textual analysis, and specifically, the study of the visual code (iconic and visual signs, tropes or rhetorical figures, etc.), which dialogues with theory, semiotics, cultural anthropology, among other sciences.Methods. In academic research, methods such as the analysis of the results of pedagogical activity, ethnographic or experiential and inductive-deductive methods were used.Results. The Didactics of a Plastic Education requires an urgent review that includes, from its most general principles and laws, to the aspects related to the selection and sequencing of content, the role of the student's plastic education in achieving a social model, the distinctions between artistic education, aesthetic education and teaching of the plastic arts in all the integrality and complexity of their discourses, the teaching-learning process, its essence and contradictions, the categorical system of the teaching-learning process, among other fundamental aspects. The present study contributes to this rethinking of the theoretical and methodological postulates of the Didactics of Plastic Education, as it proposes as an objective: to argue the didactic principle of the unity between appreciation, analysis and textual creation in the teaching-learning process of the visual image analysis.Conclusion. This argument constitutes a theoretical contribution to the science, and clarifies, while unifying, criteria and procedures in the pedagogical practice of artists, teachers, instructors and masters of the plastic arts.